Woolly hair in twins. - Rajani, H.S.; Narayanappa, D. (European Journal of Pediatric Dermatology, 2022)
Woolly hair (WH) syndrome refers to a group of congenital defects of the hair structure characterized by very curly hair in non-black African individuals. The defect can be localized or widespread, it can be familial, and it can also be associated with systemic manifestations in various syndromes. The current report describes a case of familial generalized WH in a 13-year-old girl and her older twin.